Effect of thermal treatment on the localized corrosion behavior of alloy 718 (UNS N07718) - Rebak, R.; Rincón-Ortíz, M.; Iannuzzi, Mariano; Kappes, M.; Mishra, A.; Rodriguez, M. (European Federation of Corrosion, 2014)
Nickel (Ni) based Alloy 718 (UNS N07718) is used extensively for Oil & Gas sour applications requiring yield strength levels in excess of 1000 MPa, mainly in the heat treated high strength condition for downhole and wellhead accessories and other components. It was of interest to determine how age hardening heat treatments affect the corrosion behavior of N07718. Alloy 718 was tested in the as-received condition and under the oil & gas API6A718 one step aging condition and the traditional two-step​ aging condition. The electrochemical tests were performed in 3.5% NaCl solution and in the NACE TM0177 Solution A (5% NaCl + 0.5% acetic acid). Immersion tests according to ASTM G 48D were used to determine the critical crevice temperature of the alloy. Laboratory results showed that the heat treatment performed to increase the strength of the alloy produced a slight decrease in the resistance to localized corrosion.